A Strongly Coupled Cluster Heterostructure with Pt–N-Mo Bonding for Durable and Efficient H2 Evolution in Anion-Exchange Membrane Water Electrolyzers - Zhou, Wenbo; Huang, Yichao; Cai, Hanqing; Wang, Tao; Li, Haitao; Zhang, Chao; Zhao, Lianming; Chen, Lulu; Liao, Meihong; Tang, Zhiqing; Chen, Kai; Gu, Jing; et al. (Nano-Micro Letters, 2025)
Creating strongly coupled heterostructures with favorable catalytic activities is crucial for promoting the performance of catalytic reactions, especially those involve multiple intermediates. Herein, we fabricated a strongly coupled platinum/molybdenum nitrides nanocluster heterostructure on nitrogen-doped reduced graphene oxide (Pt/Mo₂N–NrGO) for alkaline hydrogen evolution reaction. The well-defined Pt-containing Anderson-type polyoxometalates promote strong interfacial Pt–N–Mo bonding in Pt/Mo2N–NrGO, which exhibits a remarkably low overpotential, high mass activity, and exceptional long-term durability (> 500 h at 1500 mA cm⁻2) in an anion-exchange membrane water electrolyzer (AEMWE). Operando Raman spectroscopy and density functional theory reveal that pronounced electronic coupling at the Pt/Mo₂N cluster interface facilitates the catalytic decomposition of H2O through synergistic stabilization of intermediates (Pt–H* and Mo-OH*), thereby enhancing the kinetics of the rate-determining Volmer step. Techno-economic analysis indicates a levelized hydrogen production cost of 2.02 kg⁻1, meeting the US DOE targets. Our strategy presents a viable pathway to designing next-generation catalysts for industrial AEMWE for green hydrogen production. Highlights: 1 A strongly coupled platinum/molybdenum nitrides nanocluster heterostructure has been prepared by using Pt-containing Anderson-type polyoxometalates as precursors. 2 The pronounced electronic coupling at the Pt/Mo2N cluster interface facilitates the catalytic decomposition of H2O through synergistic stabilization of Pt-H* and Mo-OH*. 3 The optimized Pt/Mo2N-NrGO exhibits a remarkably low overpotential, high mass activity, and exceptional long-term durability (>500 h at 1500 mA cm-2) in a practical anion-exchange membrane water electrolyzer.